Cinema: mudanças de hábito e sociabilidade no espaço urbano de Uberlândia 1980 a 2000 - Castro, Kellen Cristina Marçal de (2008)
This study intend to reflect about the sociabilities s construction linked in the urban s transformations of Uberlândia s city in the Minas Gerais state, in the 1980 and 2000 period. The space reorganization become possible new forms of sociabilities, experiences and social practices that are connected with the formation of new references wich breaks and permanences are confronted. In this process, the action of going to the cinema also had significant chances in the same period. This changes was not only because the tecnology s inovation, particularly accelerated in the last decades of last century. It is not about to reduce the relevance of this aspect, however is when incorporated in a set of transformations that are perceived the habit of going to the cinema as a social practice. In this meaning that the discussion about the space of the cinema s room in Uberlândia gain dimension in the significant lócus of sociabilities s construction. The activities of social interaction in the city didin t restrict, exclusivement, the cinema s room. Bars, restaurants, clubs, churches, squares. And others, also were and are related as the construction s sociabilities s space. Privilege and to become a problem the sociabilities s construction related to the action of going to the cinema are caused by the destruction of a space established and the construction and the deslocation for a new local according to considerated modern standards. According to the study, is perceived the bankruptcy process of the large central rooms, the interaction with the rooms in the shopping-center that end up with the extinction of the firsts by the enlargement of the seconds. This space become not only a place where people live together but as a reference point to the citizens.